THE COMPLEXITY OF GOVERNING FISHING VILLAGES IN THE BAGAN AREAS OF SELANGOR, MALAYSIA - Mohamed, Mohd Zin; Hassan, Norhaslina (PLANNING MALAYSIA, 2017)
This paper examines the current administrative structure that deals with informal fishing villages in Selangor aiming to identify the governance issues of thesecommunities from the local-, district-, state- and federal-level perspectives. Data collection techniques employed were field observations conducted through site visits, in-depth interviews with the state and local planning officials, and focus group discussions involving chairpersons of the Village Development and Security Committees (VDSC). The analysis reveals a sizable number of entities involved in the governance and management of these fishing communities at all levels and accordingly, concludes by outlining a more strategic administrative structure that could effectively govern informal fishing villages that is applicable to Selangor and beyond.